2016
DOI: 10.1007/s11240-016-1028-z
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid stimulates the oxidative responses and triterpene production in Jatropha curcas cell suspension cultures through mevalonate as biosynthetic precursor

Abstract: Jatropha curcas has considerable potential for production of biodiesel and secondary metabolites with medicinal uses. Herein, J. curcas cell suspension cultures were established to study the effect of jasmonic acid (JA) elicitation on triterpene production and oxidative responses. Cell cultures grown in dark conditions reached maximum biomass accumulation at the 12th day of culture (14.3 ± 0.45 g DW L -1 ) with a specific growth rate l = 0.131 d -1 . Elicitation with JA (200 or 400 lM) on 4-days-old cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…According to Zaragoza-Martinez et al, the application of jasmonic acid triggered oxidative reactions in Jatropha curcas cell suspension culture, leading to elevated levels of hydrogen peroxide (H 2 O 2 ), along with an increase in malondialdehyde levels. Additionally, the study observed heightened activity of catalase, peroxidases, and ascorbate peroxidase in response to JA treatment [59]. The exposure of plant cells to elicitor treatment triggers a cascade of events, starting with signal transduction from the plasma membrane's surface and leading to the production of reactive oxygen species (ROS) [63].…”
Section: Antioxidant Enzymes Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zaragoza-Martinez et al, the application of jasmonic acid triggered oxidative reactions in Jatropha curcas cell suspension culture, leading to elevated levels of hydrogen peroxide (H 2 O 2 ), along with an increase in malondialdehyde levels. Additionally, the study observed heightened activity of catalase, peroxidases, and ascorbate peroxidase in response to JA treatment [59]. The exposure of plant cells to elicitor treatment triggers a cascade of events, starting with signal transduction from the plasma membrane's surface and leading to the production of reactive oxygen species (ROS) [63].…”
Section: Antioxidant Enzymes Quantificationmentioning
confidence: 99%
“…Optimal enzyme activities (POD: 4.84 ± 0.02; SOD: 0.779 ± 0.012 nM/min/mg FW) were observed in cultures elicited with CHT 4 and JA 3 (POD: 4.97 ± 0.04; SOD: 0.812 ± 0.017 nM/min/mg FW) compared to the control (POD: 2.31 ± 0.01; SOD: 0.55 ± 0.007 nM/min/mg FW) (see Figure 5A,B). Earlier research findings suggest that chitosan and jasmonic acid potentially enhances SOD and POD activities in cell suspension cultures, as well as in callus cultures of different plant species [28,37,[59][60][61][62]. A report by Fan et al indicates the involvement of POD and SOD in mediating chitosaninduced stress in cell suspension cultures of Betula platyphylla Suk.…”
Section: Antioxidant Enzymes Quantificationmentioning
confidence: 99%
“…Therefore, it is necessary the use of chemical analysis techniques to isolate and identify the extracted plant metabolites (Hernandez & Sarlah, 2019). There are a few cases where the use of the plant cell culture of Jatropha curcas has allowed the production of bioactive compounds (Alvero-Bascos & Ungson, 2012;Mahalakshmi, Eganathan & Parida, 2013;Nassar et al, 2013;Zaragoza-Martínez et al, 2016); the study of the culture at different stages of toxic and non-toxic varieties generates the opportunity to design biotechnological models for production of bioactive compounds i.e., terpenoids, alkaloids, flavonoids (Abdelgadir & Van Staden, 2013;Sabandar et al, 2013), providing opportunities for new drugs discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is necessary the use of chemical analysis techniques to isolate and identify the extracted plant metabolites (Hernandez & Sarlah, 2019). There are a few cases where the use of plant cell culture of Jatropha curcas has allowed the production of bioactive compounds (Alvero-Bascos & Ungson, 2012;Mahalakshmi, Eganathan & Parida, 2013;Nassar, El-Ahmay & Al-Azizi, 2013;Zaragoza-Martínez et al, 2016), the study of the culture at different stages of toxic and non-toxic varieties, generate the opportunity to design biotechnological models for production of bioactive compounds i.e. terpenoids, alkaloids, flavonoids (Abdelgavir & Van Staden, 2013;Sabandar et al, 2013) providing opportunities for new drugs discovery.…”
Section: Introductionmentioning
confidence: 99%